2006
DOI: 10.1038/nature04983
|View full text |Cite
|
Sign up to set email alerts
|

Archaea predominate among ammonia-oxidizing prokaryotes in soils

Abstract: Ammonia oxidation is the first step in nitrification, a key process in the global nitrogen cycle that results in the formation of nitrate through microbial activity. The increase in nitrate availability in soils is important for plant nutrition, but it also has considerable impact on groundwater pollution owing to leaching. Here we show that archaeal ammonia oxidizers are more abundant in soils than their well-known bacterial counterparts. We investigated the abundance of the gene encoding a subunit of the key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

129
1,544
25
26

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,188 publications
(1,724 citation statements)
references
References 26 publications
129
1,544
25
26
Order By: Relevance
“…2). The isotopic enrichment of archaeal lipids relative to methane is best explained by additional biological sources of these compounds, for example, from heterotrophic archaea 45 or autotropic archaea such as ammonium-oxidizing thaumarcharchaea 46 . Alternatively, the incorporation of DIC rather than methane into methane-oxidizing archaeal lipids 47 could explain the observed 13 C-enriched values.…”
Section: Resultsmentioning
confidence: 99%
“…2). The isotopic enrichment of archaeal lipids relative to methane is best explained by additional biological sources of these compounds, for example, from heterotrophic archaea 45 or autotropic archaea such as ammonium-oxidizing thaumarcharchaea 46 . Alternatively, the incorporation of DIC rather than methane into methane-oxidizing archaeal lipids 47 could explain the observed 13 C-enriched values.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is important to note that we did not examine the biogeographic patterns exhibited by ammonia-oxidizing archaea (AOA) in this study. Given that such archaea are relatively abundant in soil and may play a key role in ammonia oxidation [6,7], it is clearly important to study both AOA and AOB in order to gain an integrated understanding of how the composition of these communities may influence ammonia oxidation rates in soil.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, unlike many other bacterial taxa found in soil, the group is represented by a relatively large number of cultured isolates. In addition, the AOB, along with the ammonia-oxidizing archaea [6,7], perform a rate-limiting step of nitrification and play a key role in the regulation of soil nitrogen dynamics. For this reason, the study of AOB biogeography may have direct relevance to studies of soil biogeochemistry given that distinct AOB groups are likely to have different physiological and ecological attributes [8].…”
Section: Introductionmentioning
confidence: 99%
“…The recent observation showed that AOA are more abundant than AOB in marine ecosystems (Francis et al 2005) and soil ecosystems (Leininger et al 2006) and might be responsible for large part of ammonium oxidation. So the existence scope of anammox and ANME coupled to denitrification maybe much larger than our previous view from anoxic/subanoxic zone to more anaerobic zone as long as alternative electron donors (ammonium, formate, acetate, propionate, or Fe(II)) and acceptors (nitrate, nitrite, Fe(III), and Mn(IV)) are available .…”
Section: Role Of Nitrite Formationmentioning
confidence: 99%